Partial Purification of Leucine Aminopeptidase and its Correlation with Some Biochemical Parameters in Sera of Subclinical Hyperthyroidism and Hyperthyroidism Patient - Noorhan Khalid Shafeeq (Journal of Global Pharma Technology, 2019)
The study aimed to purify of Leucine aminopeptidase (LAP) from sera of hyperthyroidism patients and its relation to some thyroid hormones (TSH, T3, T4) of subclinical hyperthyroidism and hyperthyroidism patients with lipid peroxidation levels that may be play a role in this diseases. Specimens were collected during the time from Nov 2017   until Jan 2018 from Endocrine and Diabetes Center, blood samples were   collected from fifty healthy control and one hundred patients, patients were divided into two groups consisted of (50) with hyperthyroidism and (50) with subclinical hyperthyroidism. The aged for all subjects ranged (15-60) years with body mass ranged ((25- 29) kg/m2. The purification is done by addition of ammonium sulfate, dialysis, ion exchange chromatography by using DEAE -Sepharose and gel filtration chromatography by using Sepharose 6B. FT3, FT4, TSH, LAP, peroxynitrite, malondialdehyde were determined. Results showed the precipitate and concentrated protein appeared five peaks after eluted with Tris- HCl (50 mM, pH 7.0 in ion exchange column, LAP located in the first peak (wash fraction) and the second peak (elution fraction eluted with 0.1 M NaCl), also, results showed single peak for both first and second peaks after eluted in gel filtration chromatography following steps by using sodium dodecyl sulfate-polyacrylamide gel. As well as results showed a non- significant elevation in   BM, FT3 and   FT4 in subclinical-hyperthyroidism group when compared to the control group. And a highly significant elevation in LAP, peroxynitrite and MDA levels in the patient group compared to the control group, while a highly significant decrease in TSH   levels was found in the patient group compared to the control group. Results showed a non-significant elevation in BMI in hyperthyroidism group when compared to the control group., also, showed a highly significant elevation in FT3, FT4 LAP, peroxynitrite and MDA levels in the patient group compared to the control group, while a highly significant decrease in TSH levels was found in the patient group compared to the control group. From this study, it is concluded   Leucine aminopeptidase    which partial purification from sera of hyperthyroidism   patients   by ion exchange chromatography and gel filtration   chromatography   have  two  isoenzymes  ,also, concluded a highly significant elevation in LAP, peroxynitrite and MDA levels in the patient group compared to the control group , in addition to their correlation with thyroid hormone in the patient group, compared to the control group indicate that  these parameters have an effect on these diseases.Keywords: Leucine aminopeptidase, Subclinical hyperthyroidism, Hyperthyroidism, Subclinical hypothyroidism, Hyperthyroidism, Lipid peroxidation.